Effect of the CXCR2 antagonist danirixin on symptoms and health status in COPD. Issue 4 (4th October 2018) - Lazaar, Aili L.; Miller, Bruce E.; Tabberer, Maggie; Yonchuk, John; Leidy, Nancy; Ambery, Claire; Bloomer, Jackie; Watz, Henrik; Tal-Singer, Ruth
Approximately one-third of patients with chronic obstructive pulmonary disease (COPD) have chronic mucus hypersecretion (CMH) [1], often referred to as chronic bronchitis. Despite treatment with inhaled medications and other therapies, such as expectorants or methylxanthines, patients with CMH may continue to experience exacerbations, substantial symptom burden and poor health status [1]. CXCR2 antagonists are effective in multiple preclinical and human models of airway inflammation [2–5]. Danirixin is a competitive, reversible, oral CXCR2 antagonist that has been well tolerated in healthy subjects and in patients with influenza [6, 7]. We report the results of a 52-week Phase 2 study conducted in Germany and the USA (GSK protocol 200163; ClinicalTrials.gov identifier NCT02130193) assessing the effects of danirixin when added to standard-of-care inhaled medications in participants with symptomatic COPD. Participants with a forced expiratory volume in 1 s (FEV1 ) ≥50% of predicted normal and a history of two exacerbations in the prior 12 months, or one exacerbation and elevated plasma fibrinogen ≥3 mg·mL −1, as well as a history of chronic cough and/or mucus hypersecretion on most days for at least the previous 3 months prior to screening, were eligible. Full inclusion and exclusion criteria are available online at clinicaltrials.gov. The study was approved by the Western Institutional Review Board (Puyallup, WA, USA) and the Ethikkommission I, Ärztekammer Schleswig-Holstein (Bad Segeberg, Germany). Written informed consent was obtained from all participants. Danirixin was associated with improved respiratory symptoms and health status in patients with mild-to-moderate COPD http://ow.ly/5m6P30luwfh